The Effect of IOT (Internet of Things) on Green Operation for Two Hotels in Palangkaraya 2025 - Gilbert Aurelio Lundjo; Suwarno Suwarno (Publikasi Indonesia, 2025)
The integration of Internet of Things (IoT) technology and green principles offers promising prospects for the tourism industry to improve destination quality and operational efficiency. IoT provides innovative solutions in tourism governance, including the application of digital technology in the hospitality sector. Through a network of interconnected sensor devices and communication systems, IoT enables comprehensive information collection, real-time monitoring, and management of various operational aspects. This research also examines study findings related to the influence of employee behavior on customer service performance. Good hotel operations require assurance of data privacy and security, resolution of technology compatibility issues, and large investments supported by environmentally sound management governance (green operations). Implementation of green operations is proven to have a significant and positive impact on environmental performance. The study concluded that the full implementation of internal green management mediated the relationship between stakeholder pressure and environmental performance outcomes. Although the integration of IoT and green effect faces challenges, its potential benefits in developing Palangka Raya City as a tourist destination make it a strategy with great potential for future progress